PENERAPAN REALISTIC MATHEMATICS EDUCATION (RME) DALAM MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA - Nurhayati Nurhayati; Dessy Rizki Suryani; Rian Ade Pratama; Abdul Rachman Taufik (Science Map Journal, 2022)
This research is a classroom action research that aims to increase interest and achievement in learning mathematics through the application of an approach Realistic Mathematics Education (RME). This research has been conducted in two cycles with each cycle there are 4 meetings. The subjects in the study consisted of 20 students, namely 9 male students and 11 female students in grade VII SMP in Merauke. Data collection techniques used are test techniques for achievement data and non-test techniques for interest data. The results obtained are that students' interest in learning mathematics in the first cycle is 65% or 13 students are in the good or very good category and in the second cycle the student's interest is increased to 85% or 17 students are in the good or very good category. Student achievement in the first cycle who scored above or equal to 65 is 55% or 11 students who completed and in the second cycle student achievement increased by 80% or 16 students have reached the Minimum Completeness Criteria (KKM). Based on these results it can be said that the learning model of Realistic Mathematics Education (RME) can increase the interest and learning achievement of class VII